An Act for the Regulation of the Militia of this State, at 684, § 5, pt. 7 (1782). - (:unkn) unknown (General Publisher, 1782)
Any officer or private who shall be found drunk on guard, or at any other time of duty, if an officer, be cashiered and turned into the ranks, or receive such other punishment as the court shall inflict ; if a non-commissioned officer or private, he shall be confined til sober, and serve ten days longer than he was otherwise liable to.
--
Keywords: PEACE OFFICERS